Impact of donor variables on heart transplantation outcomes in mechanically bridged versus standard recipients. (29th August 2018) - Urban, Marian; Booth, Karen; Jungschleger, Jerome; Netuka, Ivan; Schueler, Stephan; MacGowan, Guy
Abstract: OBJECTIVES: This study aimed to quantify the impact of donor variables on post-heart transplantation mortality and morbidity in recipients with and without a pretransplant left ventricular assist device (LVAD). METHODS: This is a prospective cohort study of the ISHLT Transplant Registry that includes all primary heart transplants in adult recipients (January 2005–June 2013, n  = 15 532). All recipients were divided into patients with a durable continuous-flow LVAD (LVAD recipient, n  = 3315) and without mechanical support (standard recipient, n  = 12 217). Donors were classified as high risk ( n  = 3751) and low risk ( n  = 11 781). Transplants were categorized into low-risk donor/standard recipient ( n  = 9214), high-risk donor/standard recipient ( n  = 3003), low-risk donor/LVAD recipient ( n  = 2567) and high-risk donor/LVAD recipient ( n  = 748). Outcomes prior to discharge, survival at 5 years and freedom from complications were computed for each group. RESULTS: LVAD recipients experienced more episodes of infection, stroke and acute rejection with both low- ( P  < 0.001, P  < 0.001, P  < 0.001) and high-risk donors ( P  < 0.001, P  = 0.008, P  = 0.028) prior to transplant discharge. Within standard recipients, a higher rate of primary graft failure ( P  = 0.035), infection ( P  = 0.001), dialysis ( P  = 0.012), acute rejection ( P  = 0.037) and less freedom from cardiac allograft vasculopathy ( P  < 0.001) and malignancy ( P  = 0.004) was observed with high-risk donors. Within LVAD recipients, no differences in complications prior to discharge or long-term morbidity were detected between low- and high-risk donors. When compared to standard recipient/low-risk donors, all the 3 remaining categories had an increased probability of death or graft failure within 90 days: LVAD recipient/low-risk donor [hazard ratio (HR) 1.26, confidence interval (CI) 1.05–1.51; P  = 0.012], standard recipient/high-risk donor (HR 1.47, CI 1.27–1.71; P  < 0.001) and LVAD recipient/high-risk donor (HR 1.72, CI 1.32–2.24; P  < 0.001). Between 90 days and 5 years, only standard recipient/high-risk donor had an increased probability of death or graft failure (HR 1.140, CI 1.020–1.274; P  = 0.021) when compared to standard recipient/low-risk donor. CONCLUSIONS: LVAD recipients, whether with high- or low-risk donors, have worse early (but not late) survival and more early complications than those of standard recipients. We found that adverse donor characteristics are less predictive for determining the outcome of LVAD-bridged recipients than standard recipients.